Synthesis of N-unsubstituted cycloalkylimines containing a 4 to 8-membered ring. Issue 39 (26th April 2019) - Guillemin, Jean-Claude; Nasraoui, Wafa; Gazzeh, Houda
Abstract : Primary cycloalkylimines with a 4 to 8-membered ring have been synthesized by dehydrocyanation of the corresponding α-aminonitriles. Abstract : Primary cycloalkylimines with a 4 to 8-membered ring were synthesized by dehydrocyanation of the corresponding α-aminonitriles on solid potassium hydroxide via a vacuum gas–solid reaction. Imine–enamine tautomerism has been demonstrated at room temperature for the most kinetically stable derivatives.